Quand la violence parle du sexe : analyse du discours thérapeutique pour hommes violents - Letarte, Lise (Université du Québec à Montréal, 1998)
Keywords: IREF; amériques; discipline; hommes* violents; mémoires/thèses; québec; régions géographiques; sciences humaines; sexologie; thématiques; violences; violences contre les femmes*

The flowers in your dustbin: Girls in the North American punk subcultures of the 1990s - Leblanc, Lauraine (Université Emory, 1997)
Girls in male-dominated youth subcultures confront ideologies of gender which remain largely invisible and often tacitly accepted in many women's everyday lives. Punk girls choose to construct their femininity within a highly male-dominated, "masculinist," context; girls are present in such youth subcultures, but the masculine definition of their norms problematizes their participation. Thus, punk girls struggle to accommodate female gender norms within subcultural identities which are deliberately coded as "masculine." Although young women in America encounter the norms of the female gender role on a daily basis, punk girls' negotiations between the norms of femininity and those of punk open these prescriptions to critical examination which they might not otherwise be accorded. In this dissertation, I explore accounts of punk girls' engagements with both mainstream and subcultural gender norms. In constructing this account of girls' lived experiences in the punk subculture, I rely primarily upon the phenomenology, or experiential narrative, of punk girls' everyday lives. I elicited these accounts within the context of conducting participant observation in the punk scenes of four North American cities (Atlanta, Montreal, New Orleans, and San Francisco) from 1993 to 1995, conducting ethnographic interviews with forty punk girls. In the following, I explore various facets of punk girls' engagements with gender norms, including punk girls' narratives of engagement with the subculture; the construction of punk as a discourse of masculinity; punk girls' stylistic, behavioral, and discursive reconstructions of femininity; punk girls' experiences of public harassment and sexual harassment, and their strategic responses to these. I argue that these girls use the punk subculture in order to carry out resistances to varied forms of gender oppression, thereby developing stronger self-concepts in the face of adversity.
Accès par ProQuest
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; atlanta; discipline; ethnographie; genre; harcèlement sexuel; masculinisme; montréal; mémoires/thèses; nouvelle-orléans; patriarcat; philosophie; périodes historiques; régions géographiques; résistance; san francisco; sciences humaines; sofia; systèmes d'oppression; thématiques; violences

Science, conscience et action : vingt-cinq ans de recherche féministe au Québec - Dagenais, Huguette (Les éditions du remue-ménage, 1996)
Après un quart de siècle de néoféminisme, on connaît encore mal la recherche féministe et l’ampleur du travail accompli par ces chercheuses. Les auteures examinent ici les travaux qui ont porté sur la famille, la conciliation travail-famille et sur l’emploi, ceux qui ont documenté des aspects particuliers de la santé des femmes et de la violence conjugale ainsi que les nombreuses études produites dans le domaine de l’éducation. Elles mettent également en lumière les changements et les résistances révélés par les recherches dans le champ religieux, le champ politique, celui du droit de même que dans le domaine des communications. Ce faisant, elles rendent manifestes les caractéristiques de la recherche féministe québécoise, notamment les liens établis par les chercheuses entre théorie et pratique, recherche et action. Des textes de Pierrette Bouchard, Anita Caron, Renée Cloutier, Christine Corbeil, Huguette Dagenais, René B.-Dandurand, Francine Descarries, Louise Guyon, Thérèse Hamel, Geneviève Martin, Karen Messing, Josée Néron, Ann Robinson, Armande Saint-Jean, Diane-Gabrielle Tremblay et Manon Tremblay.
Keywords: 1900-1999; amériques; conciliation famille-travail; discipline; droit; fem1000; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; santé; science des religions; science politique; sciences humaines; thématiques; théologie; violences; violences contre les femmes

Taboo: Sex, identity, and erotic subjectivity in anthropological fieldwork - Kulick, Don; Willson, Margaret (Routledge, 1995)
Taboo looks at the ethnographer and sexuality in anthropological fieldwork and considers the many roles that sexuality plays in the anthropological production of knowledge and texts. How does the sexual identity that anthropologists have in their "home" society affect the kind of sexuality they are allowed to express in other cultures? How is the anthropologists' sexuality perceived by the people with whom he or she does research? How common is sexual violence and intimidation in the field and why is its existence virtually unmentioned in anthropology? These are but a few of the questions to be confronted, exploring from differing perspectives the depth of the influence this tabooed topic has on the entire practice and production of anthropology. A long-overdue text for all students and lecturers of anthropology, many post-fieldwork readers will find a resonance of issues they have previously faced (or tried to avoid) and those who are still to undertake fieldwork will find articles that refer to other kinds of personal and professional experience as well as providing invaluable preparations for coping in the field.other kinds of personal and professional experience as well as providing invaluable preparations for coping in the field.other kinds of personal and professional experience as well as providing invaluable preparations for coping in the field.other kinds of personal and professional experience as well as providing invaluable preparations for coping in the field.
Keywords: anthropologie; discipline; identités; ressource en ligne; sciences humaines; sexualité; thématiques; violences; violences sexuelles

The interpretation of the flesh: Freud and femininity - Brennan, Teresa (Routledge, 1992)
The 'riddle of femininity', like Freud's reference to women's sexuality as a 'dark continent', has been treated as a romantic aside or a sexist evasion rather than as a problem to be solved. In this first comprehensive study, Teresa Brennan suggests that by placing these ideas in the context of Freud's work as a whole, we will begin to understand why femininity was such a riddle for Freud. Brennan argues that by turning to Freud's work and his concrete questions about femininity, a psychical state which occurs in men and women alike, the problem is clearly a soluble one, provided that Freud's concern with energy is taken into account. The real riddle of femininity is as much a problem for thinking about physicality as a problem for the subject who suffers from what Freud described as 'femininity's negative effects on curiosity, intelligence and activity.
Keywords: 1900-1999; discipline; fem1000; féminité; histoire; premier cycle; psychanalyse; psychologie; périodes historiques; ressource en ligne; sciences; sciences humaines; thématiques; violences

Emprise et violence maternelles: étude d'anthropologie psychanalytique - Couchard, Françoise (Dunod, 1991)
A partir d'exemples culturels et de cas empruntés à la clinique quotidienne, cet ouvrage montre les effets psychologiques d'une réduction de la personnalité féminine à sa seule fonction de reproduction : en particulier les comportements d'agression de la mère vis-à-vis de sa ou de ses filles.
Keywords: 1900-1999; anthropologie; discipline; europe; fem1000; figure de la mère; france; matrernité; premier cycle; psychanalyse; périodes historiques; régions géographiques; sciences humaines; thématiques; violences; violences familiales